The Influence of Product Quality, Brand Image and Lifestyle on Iphone Purchasing Decisions For Generation-Z in Karawang - Fitrayassa, Haekal; Savitri, Citra; Faddila, Syifa Pramudita (Westscience Press, 2024)
In Indonesia, the iPhone became the ruler of the smartphone market share of 11.81%. However, the iPhone has a relatively expensive price for teenagers or gen-z, although with a high price there are still many who crave this smartphone, this study aims umtuk determine the extent to which product quality, brand image, and lifestyle affect iPhone purchasing decisions in Generation-z in Karawang. This study uses a quantitative approach. The population studied based on domicile in Karawang, the number of samples used as many as 200 respondents. The determination of sampling technique in research is nonprobability sampling through purpose sampling. The results of this study stated that the quality of product brand image and lifestyle significantly influence the decision to buy an iPhone in Generation-z in Karawang. Further research may consider other factors such as cultural influences, social environment and price competitiveness in influencing iPhone purchase decisions.